Determination of feedback in judo by means of T-patterns - Iván Prieto Lage; Alfonso Gutiérrez-Santiago; Miguel Ángel Prieto Lage (Universidade Estadual Paulista (UNESP), 2014)
The aim of this research was to propose methodological changes in the teaching-learning process of the judo technique Deashi-harai, pointing out the most frequent technical errors committed during its performance and also its action sequences. We carried out an observational study with the participation of fifty novice judokas at the University of Vigo. We recorded them while performing the Deashi-harai technique after a previous training of four months. Data obtained were evaluated using descriptive statistics and T-patterns analysis. Thus, we indentified: a) some typical inaccuracies during the technique execution and b) a number of chained errors affecting the imbalance of the body, the position of the right foot, the sweeping action and the action of the arms. These findings allowed us to suggest some motor tasks to correct the identified inaccuracies, the sequential actions to ensure the success of the execution and several recommendations for the proper use of the feedback.